MEKANISME PENYELESAIAN SENGKETA PELANGGARAN HAK CIPTA MELALUI ARBITRASE - Dimas Mahendrayana, I Made Dwi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 1 (2020), 2020)
A copyright violation occurs when someone makes an announcement or reproduction of a work without permission from the creator or copyright holder. If this happens, the creator or copyright holder can bring his dispute to be resolved through alternative dispute resolution or arbitration. However, the Law No. 28 of 2014 concerning Copyright does not regulate the mechanism for resolving copyright disputes through arbitration. The purpose of this study is to determine the mechanism for resolving disputes over copyright infringement through arbitration and the mechanism for canceling decisions on resolving disputes over copyright infringement through arbitration. This research uses normative legal research. From the results of the study, the initial stage of the mechanism of resolving disputes over copyright infringement through arbitration begins with the submission of the request for arbitration. Furthermore, the applicant makes a claim letter and proceed with the selection and appointment of the arbitrator. Then the arbitration examination. The final stage of the trial in arbitration is the submission of the award to the parties, and continued with the implementation of the arbitration award. An arbitration award can be requested to be canceled. The mechanism for cancellation of a national arbitration award begins by registering an arbitration award for cancellation at the Registrar's Office of the District Court. Then the court will examine the facts about whether or not the reasons stated by the applicant to cancel the arbitration award. If no, the application is rejected, but if the facts are found, the court is only authorized to cancel part of the arbitration award.